THE RESPONSE OF BRICS TRADE INTEGRATION TO GEOPOLITICAL RISKS - Sohag, Kazi; Islam, Md Monirul; Mariev , Oleg (Bank Indonesia, 2024)
Mounting geopolitical risks have led over time to a reorientation of trade integrations across different economic blocs. As one of the increasingly dominant global blocks, the organisation comprised of Brazil, Russia, India, China, and South Africa (BRICS) has intensified their trade integration. Therefore, we conducted a thorough analysis of how BRICS countries’ multilateral trade integration responded to geopolitical risk events from January 1996 to December 2021. To achieve this, we utilized a sophisticated econometric method, specifically the cross-quantilogram approach, to analyse high frequency data due to their non-normal and fat-tailed features. Our study confirms the proposition that geopolitical risks strengthened trade integration within the BRICS bloc. Specifically, our findings show that the volume of exports from one economy to another responded positively at lower to medium quantiles of exports and lower geopolitical risks, considering a 12–36-month horizon. Moreover, we found that the quantity of exports from Russia to China was higher in the presence of higher geopolitical risks. Our study demonstrates that geopolitical risks can create a sense of shared identity and mutual interest among the BRICS countries, fostering greater cooperation and trade integration.